2001
DOI: 10.1007/s002280100305
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of viral antibodies after administration of intravenous immunoglobulin in patients with chronic lymphocytic leukaemia or multiple myeloma

Abstract: The pharmacokinetic parameters of the IgG antibodies calculated after administration of the novel IVIG preparations to patients with CLL and multiple myeloma are in close agreement with data obtained from healthy volunteers and with values of native IgG, suggesting that the production process did not impair clinically relevant characteristics of the viral antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Denosumab exhibits non‐saturable, linear PK at doses greater than 1.0 mg kg −1 which, as discussed above, may be explained by proteolytic catabolism via the reticuloendothelial system and endothelial cells or binding to FcRn. These proposed mechanisms of elimination are further confirmed by the observation of similar mean apparent CL/ F values (0.07–0.10 ml h −1 kg −1 ) in clinical studies of denosumab at higher doses (1.0–3.0 mg kg −1 ) to that reported for other endogenous immunoglobulins (CL/ F = 0.09–0.12 ml h −1 kg −1 ) .…”
Section: Discussionsupporting
confidence: 77%
“…Denosumab exhibits non‐saturable, linear PK at doses greater than 1.0 mg kg −1 which, as discussed above, may be explained by proteolytic catabolism via the reticuloendothelial system and endothelial cells or binding to FcRn. These proposed mechanisms of elimination are further confirmed by the observation of similar mean apparent CL/ F values (0.07–0.10 ml h −1 kg −1 ) in clinical studies of denosumab at higher doses (1.0–3.0 mg kg −1 ) to that reported for other endogenous immunoglobulins (CL/ F = 0.09–0.12 ml h −1 kg −1 ) .…”
Section: Discussionsupporting
confidence: 77%
“…Previously published kinetics clearly show an exponential antibody decrease well described by a terminal elimination half‐life. Indeed, the measured half‐lives of 25 ± 6 and 26 ± 6 days in the present study perfectly fit the reported terminal elimination half‐lives of 22 to 25 days 22–24…”
Section: Discussionsupporting
confidence: 89%
“…This implies that the reaction of certain initial HBsAg levels and certain immunoglobulin doses generate calculable immunocomplex, HBsAg and anti-HBs levels. However, in-depth analysis of our kinetics' characteristics and previously published data [23,47] suggest that the equilibrium reaction is affected by different factors: anti-HBs levels are influenced by anti-HBs distribution to extra-vascular compartments and drainage fluids and by breakdown. HBsAg seems to be released to circulation by extra-vascular reservoirs.…”
Section: Discussionmentioning
confidence: 76%